Modeling the Keys to Team’s Success in the Women’s Chinese Basketball Association - Yi, Qing; Zhang, Shaoliang; Fang, Wenxuan; Gómez-Ruano, Miguel-Ángel (Frontiers in Psychology, 2021)
The technical characteristics of women’s basketball may differ from men’s basketball, and there is a need to identify the key performance indicators (KPIs) that contribute to the success of women’s teams. The aim of the current study was to examine and quantify the relationships between technical performance indicators and match outcome in elite women’s basketball using both linear and non-linear statistical methods, the effectiveness of the two methods was compared as well. A total of 136 matches (n = 272 teams’ observations) in the regular season of Women’s Chinese Basketball Association (WCBA; season 2020–2021) were analyzed using multiple linear regression (MLR) and quantile regression (QR). Results showed that two-point percentage, offensive rebounds, assists and turnovers had significant effects on the match outcome for both MLR and QR analysis. No significant relationships were observed between match outcome and three-point percentage, steals, and fouls. The results between MLR and QR analysis were different in free-throw percentage, defensive rebounds and blocks. Current results highlighted QR analysis is an advanced statistical model more powerful than the traditional linear method for the identification of KPIs. The identified KPIs may help coaches to develop more specific training interventions and match strategies during match play.